Baby Massage Therapy Using Lavender Aroma Oil Affects Baby's Sleep Length: Terapi Pijat Bayi Menggunakan Minyak Aroma Lavender Berpengaruh pada Lama Tidur Bayi - Asriwidyayanti; Tempali, Sri Restu; Lisnawati; Pani, Widya; Hadriani; Patuju, Isda Rahmi (Napande: Jurnal Bidan, 2025)
Background: Sleep disorders for children can affect their emotions and behavior, to overcome the quality of sleep that is not optimal, one of which is with massage. Massage using lavender-scented oil can have a relaxing effect on the baby's body. Objective: To determine the effectiveness of the baby's sleep duration by massaging using lavender aroma oil. Methods: This study was designed to involve 30 respondents. The sample takers used simple random sampling by drawing lots based on inclusion criteria, namely babies aged 6-12 months, healthy babies and willing to be repondent, and exclusion criteria, namely sick babies requiring treatment. The study was conducted in May and June and the data were collected using questionnaires. The Wilcoxon test was used to analyze the data. Results: before the massage, 27 (90.0%) babies with insufficient sleep quality were found and there were 3 (10.0%) babies who were classified as having sufficient sleep quality. Through Wilcoxon's test, his analysis found that Z is -4.690 and p-value is 0.000 (<0.05). P < 0.05 so that Ha is accepted by Ho is rejected, meaning that there is an effect of baby massage using lavender-scented oil on the length of sleep of babies aged 6-12 months. Conclusion: Baby massage using lavender-scented oil is optimal for the length of sleep of babies aged 6-12 months. Medical workers are proposed to take part in baby massage training so that they can educate and practice baby massage at the posyandu